Binary Framing of Consent and Coercion of Child Marriage: A Critique - Mowri, Seama; Sultana, Rafia; Biswas, Subas; Azmi, Raia; Ahsan, Sairana; Rashid, Sabina F. (Young Lives, 2022)
This book chapter was published in the book named Dreaming of a Better Life Child Marriage Through Adolescent Eyes and the definite version is available at : https://www.younglives.org.uk/sites/www.younglives.org.uk/files/YL-DreamingOfBetterLife-LowRes_0.pdf